KOMUNIKASI PERSUASIF TIM TASYKIL JAMAAH TABLIGH DALAM MENYAMPAIKAN DAKWAH DIKALANGAN WARGA MUSLIM (studi di kelurahan tuah karya kecamatan tampan kota pekanbaru) - Niko Hayadi; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Jamaah tabligh is an Islamic groups which focuses on improving the quality of faith and pious charity by moving and conveying the massage of the importance of faith and pious charity to all Muslims wherever they are. Jamaah tabligh is basically a designatios of people for those who are engaged in Da’wah activity in this group. However, the name of tabligh not the name that is inaugurated but only the familiar appellation so that the people knows it as jamaah tabligh. Tasykil group is a small group of jamaah tabligh which are selected based on discussion with the considerations of mastering a lot of Da’wah material and having done khuruj frequently or out to do house to provide information about Da’wah activity they do.The method used in this research is descriptive qualitative method. Data was collected trough interviews, partisipant observation, and documentation. The location of this research in Tuah Karya Village, District of Tampan, Pekanbaru. The number of informants for this study is 12 respondents. Sampling is done by using porposive sampling technique. The author conducts are data analysis by using Huberman and Miles theory and for checking the data validity, the author uses data triangulation and technique.The results of how persuasive communication of tasykil jamaah tabligh groups are applied to the muslim’s residents are divided to: The elements of persuasive communication of tasykil jamaah tabligh groups and The techniques of persuasive communication of tasykil jamaah tabligh groups. And The Factors which are motivation and environment. In doing the Da’wah activity among the muslim’s residents, the tasykil jamaah tabligh groups are using several methods, including; khuruj method (out to do Da’wah) and Maqomi Da’wah (local).Kerwords : Persuasive Communication, Tasykil Jamaah Tabligh Gropus, Da’wah